2018
DOI: 10.3389/fpsyg.2018.02555
|View full text |Cite
|
Sign up to set email alerts
|

Perception of a Perpetrator as a Successful Person Predicts Decreased Moral Judgment of a Rape Case and Labeling it as Rape

Abstract: Rape cases of celebrities and other influential figures have caught the public eye in recent years. Following the media attention to these cases, people made strong judgments either believing or doubting the victims. Even though some of these men were convicted, they tended to receive little jail time and continued to enjoy people’s sympathy, as in the case of the Hungarian national swimming-coach. We examined whether opinions about the coach’s rape were affected by rape myth acceptance (RMA) and the perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(105 reference statements)
4
15
1
Order By: Relevance
“…Yet, the very public status of these men also tends to hinder this opportunity, exemplifying how power differentials between men and women are played out in the public arena. In the case of celebrities, these power differentials correspond to the double standards placed on the famous men who can feed their admiration into rape myths to escape accusations in the public mind, versus the anonymous women who are positioned in these rape myths as the deserving victim (Nyúl et al 2018).…”
Section: Rape Genres and Celebritiesmentioning
confidence: 99%
“…Yet, the very public status of these men also tends to hinder this opportunity, exemplifying how power differentials between men and women are played out in the public arena. In the case of celebrities, these power differentials correspond to the double standards placed on the famous men who can feed their admiration into rape myths to escape accusations in the public mind, versus the anonymous women who are positioned in these rape myths as the deserving victim (Nyúl et al 2018).…”
Section: Rape Genres and Celebritiesmentioning
confidence: 99%
“…We argue that this context can create norms that sanction rape myth acceptance and can therefore affect the degree to which people label cases as rape. As previous research has shown, such labeling can fundamentally affect the overall evaluation of the case and the treatment of perpetrators and survivors (Nyúl et al, 2018).…”
Section: Research Aims and Hypothesesmentioning
confidence: 99%
“…Therefore, McMahon and Farmer (2011, 19 items) changed the items, updated the language, and eliminated three subscales from IRMAS and constructed the Updated Illinois Rape Myth Acceptance Scale (short form) to measure more contemporary and subtle forms of rape myths. It was used, for example, for longitudinally investigating the long-term effects of violent video gameplay on sexist attitudes and rape myth acceptance (Kühn et al, 2019), and exploring the relation between prior victimization, just world beliefs, and rape myth acceptance (Vonderhaar & Carmody, 2015), and examining the role of rape myth acceptance in the evaluation of real rape cases (Nyúl et al, 2018), and exploring the relation between rape myth acceptance and bystander behavior (Bennett et al, 2017).…”
Section: Measuring Rape Myth Acceptancementioning
confidence: 99%